AQUÁTICAS INSTALLATIONS IN THE CITY OF CANOAS, RS: A VISION ADMINISTRATIVE. (Fiep Bulletin - online, 2014)
The present study it is presented as descriptive with a qualitative boarding. As objective it was traced: presenting the sports administrations in the city of Canoas, Rio large South in the perception of managers of plants. Sample was composed of three managers of these spaces. As an instrument used is the questionnaire adapted from Moreno (1996). Research results were as follows: the administration of aquatic plants of the city of Canoas is carried through by the proper proprietors or relatives of those, in this direction thereby maintaining complete control over everything that happens. Most of the managers are satisfied with the operation of the plant and believe that their subordinates held in general a good job. It follows that the environment of aquatic plants as well as the professionals who work can strongly influence the motivation and the permanence of the participants. And to be considered a enterprise that it stimulates and is generating motivation and growth is important, that everyone involved, seek attitudes and daily operations that meet expectations.
Keywords: administration; aquatic activities; Canoas